Agreement of three CT perfusion software packages in patients with acute ischemic stroke: A comparison with RAPID. Issue 156 (November 2022) - Lu, Qingqing; Fu, Junyan; Lv, Kun; Han, Yan; Pan, Yuning; Xu, Yiren; Zhang, Jun; Geng, Daoying
Abstract: Purpose: To compare ischemic core volume (ICV) and penumbra volume (PV) measured by MIStar, F-STROKE, and Syngo.via with that measured by RAPID in acute ischemic stroke (AIS), and their concordance in selecting patients for endovascular thrombectomy (EVT). Methods: Computed tomography perfusion (CTP) data were processed with four software packages. Bland–Altman analysis and intraclass correlation coefficient (ICC) were performed to evaluate their agreement in quantifying ICV and PV. Kappa test was conducted to assess consistency in the selection of EVT candidates. The correlation between predicted ICV and segmented final infarct volume (FIV) on follow-up images was investigated. Results: A total of 91 patients were retrospectively included. F-STROKE had the best consistency with RAPID (ICV: ICC = 0.97; PV: ICC = 0.84) and Syngo.via had the worst consistency (ICV: ICC = 0.77; PV: ICC = 0.66). F-STROKE had the narrowest limits of agreements both in ICV (−27.02, 24.40 mL) and PV (−85.59, 101.80 mL). When selecting EVT candidates, MIStar (kappa = 0.71–0.88) and F-STROKE (kappa = 0.84–0.90) had good to excellent consistency with RAPID, while Syngo.via had poor consistency (kappa = 0.20–0.41). ICV predicted by MIStar was correlated strongest with FIV (r = 0.77). Conclusions: F-STROKE is most consistent with RAPID in quantitative ICV and PV. F-STROKE and MIStar exhibit similar EVT candidate selection to RAPID. Syngo.via, for its part, seems to have overestimated ICV and underestimated PV, leading to an overly restrictive selection of EVT candidates.